Pengaruh Regulasi Pemerintah, Tekanan Pemangku Kepentingan, dan Pelaksanaan Tanggung Jawab Sosial terhadap Penerapan Prinsip ESG pada Perusahaan di Indonesia - Riani Dwi Antika; Riska Dwi Arini; Syifa Yuniatin Arini; Zulfaturrokhmah Aulia; Dien Noviany Rahmatika (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the influence of government regulations, stakeholder pressure, and the implementation of corporate social responsibility (CSR) on the application of Environmental, Social, and Governance (ESG) principles in companies in Indonesia using a qualitative approach through the Systematic Literature Review (SLR) method on 50 published journals from 2019 to 2025. The analysis was conducted through a process of theme identification, literature screening, data extraction, and synthesis of findings. The results show that government regulations provide a structural basis for ESG implementation, but its implementation is still hampered by weak supervision and policy inconsistencies. Stakeholder pressure has proven to be a strong external factor in encouraging companies to improve transparency, accountability, and the quality of sustainability reporting. Meanwhile, the implementation of CSR contributes significantly to strengthening social and governance aspects, while also enhancing the legitimacy and reputation of companies. Overall, these three variables complement each other and simultaneously encourage more effective and sustainable ESG implementation. This research provides academic and practical contributions to understanding the determining factors for the successful implementation of ESG and the importance of synergy between regulations, social pressure, and corporate commitment to sustainable development in Indonesia